An Action Research Evaluating Artificial Intelligence (AI) Consumption among Learners of San Vicente National High School as Online Scaffold to Academic Endeavor: Experiences and Practices - Leo N. Del Valle; Clivie S. Abuzo; Jason Jay M Siga; Jelord Lufranco (Randwick International of Education and Linguistics Science Journal, 2024)
Despite the overwhelming use of the internet as an educational or informational resource, research has found that learners are woefully in need of guidance on how to use this resource effectively and subsequently identify reliable sources of information from unreliable. This study aims to determine the practices of students at San Vicente National High School in evaluating the reliability of online sources. This study employed the quantitative research design and utilized a questionnaire developed by the researchers of this study as a tool for gathering the data. The respondents of the study are 81 out of 324 digitally literate high school students enrolled at San Vicente National High School, San Vicente, Loreto, Agusan del Sur, of the academic year 2023-2024. The researchers used a stratified random sampling technique to obtain the sample size of the respondents. The findings revealed that the strategies employed by the students in evaluating the reliability of online sources are fairly practiced. It was recommended that students of San Vicente National High School be trained to critically evaluate the reliability of online sources by focusing on key factors such as consistency, authority, currency, objectivity, references, and language. Teachers should support this by providing curated lists of trustworthy sources and teaching simple practices for cross-checking information. Parental involvement is also essential in helping students develop better assessment skills, while school administrators are encouraged to organize digital literacy programs in collaboration with policymakers. Additionally, peer reviews should be encouraged to foster collaborative learning, and AI integration into the curriculum is suggested to prepare students for a future driven by Artificial Intelligence.